Manufacturing of unidirectional stitched glass fabric reinforced polyamide 6 by thermoplastic resin transfer moulding. (April 2020) - Murray, James J.; Robert, Colin; Gleich, Klaus; McCarthy, Edward D.; Ó Brádaigh, Conchúr M.
Abstract: This study aims to address barriers which remain to adoption of reactive thermoplastic resin transfer moulding in terms of knowledge and equipment. Glass fibre reinforced polyamide 6 composites with ~52% fibre volume fraction and ~1% voids were produced within 5 min using thermoplastic resin transfer moulding by injection of low viscosity monomer precursors and in-situ polymerisation. Unidirectional laminates were produced using injection pressures of around 10% of those required to achieve the same fibre volume fraction and degree of wet-out using a typical thermoset RTM resin, negating the need for expensive equipment. The equipment and process employed are described in detail and the quality and properties of the polymer matrix and composite laminates were characterised extensively in terms of chemical, thermo-morphological and mechanical properties. The paper demonstrates the high quality parts that can be achieved by accurately controlling some of the most important parameters. Graphical abstract: Unlabelled Image Highlights: In-situ polymerised polyamide composite was manufactured by resin transfer moulding. Bespoke thermoplastic resin transfer moulding equipment was designed and built. Polymer and composite properties (0° & 90°) were characterised mechanically. The longitudinal strength was superior to commercial organo-sheet. Reduced transverse strength due to the high packing density in bundles at stitch